Does soccer cleat design influence the rotational interaction with the playing surface? - Galbusera, F.; Tornese, D. Z.; Anasetti, F.; Bersini, S.; Volpi, P.; La Barbera, L.; Villa, T. (Sports Biomechanics, 2013)
Non-contact injuries in soccer players may be related to the interplay between cleat type and playing surface, and bladed shoes were often blamed for non-contact injuries with no research support. The aim of this study was to compare the rotational resistance (stiffness and peak sustainable torque) among three types of soccer cleats (metal studs, molded rubber studs, and bladed) in a controlled laboratory environment. The shoes were tested on both natural and artificial turfs under a compressive preload of 1000 N and with internal and external rotations. The three shoe models showed comparable performances with a good repeatability for each individual test on both playing surfaces. A less stiff behavior was observed for the natural turf. A tendency toward highest peak torque was observed in the studded model on natural surface. The bladed cleats provided peak torque and rotational stiffness comparable to the other models. Studded and bladed cleats did not significantly differ in their interaction with the playing surface. Therefore, soccer shoes with bladed cleats should not be banned in the context of presumed higher risk for non-contact injuries.